CEO Psychological Characteristics And Sustainability Report Disclosure In Indonesia - Indah Dzikriah, Sukmawati; Sri Andayani , Endang; Wardoyo, Cipto (Publisher Cv. Inara, 2025)
This study aims to test the upper echelon theory by examining how CEO narcissism and optimism affect sustainability report disclosure. This study uses panel data regression with Eviews 12 on sample data of 238 companies on the Indonesia Stock Exchange (IDX) that published sustainability and annual reports 2021-2023. Frim size, firm age, leverage, and profitability are included as control variables. The results indicate that CEO narcissism negatively influence on sustainability report disclosure while CEO optimism positively influence on sustainability report disclosure. The presence of the firm age control variable changes the findings. CEO characteristics no longer affect sustainability report disclosure after the addition of the company age control variable in the regression model. The results of this study has practical implications for the board of commissioners and shareholders namely the importance of considering psychological aspects, such as narcissistic traits and the level of CEO optimism, when selecting and compiling the structure of the company's board of directors.